ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN ULANG E-WALLET PADA GENERASI MILENIAL DI DAERAH ISTIMEWA YOGYAKARTA - Adhi Prakosa; Dimas Jati Wintaka (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
Based on the phenomena that happen in society, there are many e-wallet services in Indonesia but still have not adopted their effectiveness. This study aims to measure people's acceptance of GoPay e-wallet as a tool of payment in the cashless generation. To find out whether consumers are interested in using GoPay as a payment tool frequently, we using multiple linear regression analyses. The purpose of this study was to determine the effect of perceived ease of use, perceived usefulness, and experience on the intention to reuse GoPay with millennial generation samples in Yogyakarta. The results show that perceived ease of use, perceived usefulness, and experience partially and simultaneously affect the intention reusing GoPay e-wallet.